Antibody engineering for HIV therapeutics : from fusion inhibition to delivery of genetic regulators - Santos, Ana Catarina Cunha, 1986- (2017)
Tese de doutoramento, Farmácia (Biotecnologia Farmacêutica), Universidade de Lisboa, Faculdade de Farmácia, 2017